Coarse contingencies and ambiguity - Larry G. Epstein; Massimo Marinacci; Kyoungwon Seo (Theoretical Economics, 2007)
The paper considers an agent who must choose an action today under uncertainty about the consequence of any chosen action but without having in mind a complete list of all the contingencies that could influence outcomes. She conceives of some relevant (subjective) contingencies but she is aware that these contingencies are coarse—they leave out some details that may affect outcomes. Though she may not be able to describe these finer details, she is aware that they exist and this may affect her behavior.
Keywords: D81; 330; Uncertainty; states of the world; ambiguity; coarse contingencies